Keeping Memories Alive: A Decennial Study of Social Media Reminiscing, Memories, and Nostalgia - Beata Jungselius; Alexandra Weilenmann (Social Media + Society, 2023)
In this article, we present findings from an analysis of social media users’ own descriptions of having lived with social media for over a decade. In doing so, we draw upon the users’ reflections as related in data collected over 10 years. We present findings from a unique dataset of 36 stimulated-recall interviews, where we have studied the same group of informants in 2012, 2017, and 2022. While previous work on reminiscing, memories, and social media have relied on descriptions of practices as they are remembered, our approach has allowed us to follow and examine how users reflect upon their own practices over time. In this article, we focus on social media reminiscing practices and show how social media users seek and engage with previously posted social media content to reminisce and how their reflecting upon how their social media practices have evolved over time evoke ambiguous feelings. Drawing upon previous work and our own empirical material, we define and discuss social media nostalgia. We describe how social media users experience both personal social media nostalgia (referring to how I was), and historical social media nostalgia (referring to how it was) when reflecting upon past social media practices and demonstrate how social media users nostalgize as they interact with and through social media memories. Finally, we discuss our findings in relation to the interplay between reminiscing practices and technology and point to how social media memories represent a detailed insight into an ongoing social transformation of everyday life.